Diplomado de Recipientes a Presión: Módulo II (Fabricación de Recipientes a Presión Conforme a la Sección VIII, Div.1 del Código ASME) - Rivera Mendoza, Orlando R. (My University, 2007)
Objetivo General: Proporcionar los conocimientos mínimos requeridos para fabricar cualquier recipiente sujeto a presión conforme a los requisitos obligatorios establecidos en la Sección VIII, División 1 del Código ASME.
Keywords: Recipientes a presión; Fabrication codes, reference codes, addenda, sequence of fabrication requirements, effects on fabrication flow, weld joint, fabrication considerations, joint types, vessel, UW-11, UW-12, radiography, corrosion allowance, circumferential stress, material selection, welded pressure parts, UG-11, UG-44, (UCS-6 plate material), UCS-5, UG-84, material traceability, forming, roundness, UCS-79, fiber elongation, (cutting, fitting and alignment), welding limitations, UW-35, UHT-84 weld finish